A study on etiological profile of children admitted with acute encephalitis syndrome - Susmitha, Munagala; Chetty, Sanjeev; Rao, V. Sri Ruchitha (International Journal of Contemporary Pediatrics, 2025)
Background: Acute encephalitis syndrome (AES) is a neurological emergency with significant morbidity and mortality in children. AES is characterized by acute fever, altered mental status, and seizures. Japanese encephalitis (JE) is the leading cause of AES in India, with other viral, bacterial, and parasitic infections also contributing. The study aims to analyse the etiological profile, clinical presentation, and immediate outcomes in children with AES. Methods: This descriptive study was conducted in the department of pediatrics, Navodaya medical college, Raichur, Karnataka. A total of 56 children aged 1 month to 12 years with AES were included. The clinical presentation, laboratory findings, imaging, and etiological confirmation were analysed. Results: Among 56 cases, the most affected age group was infants below one year (41.1%), with a male-to-female ratio of 1.4:1. Fever (100%), altered sensorium (85.7%), and seizures (76.8%) were the most common presenting symptoms. Meningeal symptoms were seen in 32.1% of cases. Raised intracranial pressure was observed in 41.1% of cases. Mechanical ventilation was required in 32.1% of cases. Etiology was confirmed in 23.2% of cases, with bacterial infections (8.9%), tuberculosis (5.4%), and viral infections (8.9%), including varicella encephalitis (3 cases) and probable JE (2 cases). The mortality rate was 13%, while 18% had neurological sequelae. Poor Glasgow coma scale (GCS) score, need for mechanical ventilation, and hyponatremia were associated with poor outcomes. Conclusions: AES remains a major public health concern, with a significant proportion of cases having an unidentified etiology. Early diagnosis, supportive care, and identification of treatable causes can improve outcomes.